Cardiovascular risk factors, exercise capacity and health literacy in patients with chronic ischaemic heart disease and type 2 diabetes mellitus in Germany: Baseline characteristics of the Lifestyle Intervention in Chronic Ischaemic Heart Disease and Type 2 Diabetes study. (11th August 2022) - Dinges, Sophia MT; Krotz, Janosch; Gass, Felix; Treitschke, Julian; Fegers-Wustrow, Isabel; Geisberger, Marisa; Esefeld, Katrin; von Korn, Pia; Duvinage, André; Edelmann, Frank; Wolfram, Oliver; Brandts, Julia; et al.
Background: Lifestyle interventions are a cornerstone in the treatment of chronic ischaemic heart disease (CIHD) and type 2 diabetes mellitus (T2DM). This study aimed at identifying differences in clinical characteristics between categories of the common lifestyle intervention targets BMI, exercise capacity (peak V̇O2 ) and health literacy (HL). Methods: Cross-sectional baseline characteristics of patients enrolled in the LeIKD trial (Clinicaltrials.gov NCT03835923) are presented in total, grouped by BMI, %-predicted peak V̇O2 and HL (HLS-EU-Q16), and compared to other clinical trials with similar populations. Results: Among 499 patients (68.3±7.7 years; 16.2% female; HbA1c, 6.9±0.9%), baseline characteristics were similar to other trials and revealed insufficient treatment of several risk factors (LDL-C 92±34 mg/dl; BMI, 30.1±4.8 kg/m 2 ; 69.6% with peak V̇O2 <90% predicted). Patients with lower peak V̇O2 showed significantly higher ( p < 0.05) CIHD and T2DM disease severity (HbA1c, CIHD symptoms, coronary artery bypass graft). Obese patients had a significantly higher prevalence of hypertension and higher triglyceride levels, whereas in patients with low HL both quality of life components (physical, mental) were significantly reduced. Conclusions: In patients with CIHD and T2DM, peak V̇O2, BMI and HL are important indicators of disease severity, risk factor burden and quality of life, which reinforces the relevance of lifestyle interventions.